-وعي الطلبة بمنصة التعليم الإلكتروني- موودل - بوشي,فوزية (University of Eloued جامعة الوادي, 2024)
نسعى من خلال هذه الدراسة بحث وعي الطلبة بالتعليم الإلكتروني بالتركيز على فهمهم بهذا الموضوع واستجابتهم الفعلية نحو استخدام إحدى تقنياته وهي منصة موودل. تحقيقا لذلك قمنا بإجراء عمل ميداني باستخدام المقابلة الحرة على عينة قصدية مكونة من 22 طالبا بقسم علم الاجتماع، بكلية العلوم الاجتماعية بجامعة تيارت. وتوصلنا إلى أهم النتائج الآتية: _ يملك الطلبة المبحوثون معارف سطحية مع بعض التحريفات عن التعليم الإلكتروني. - للطلبة المبحوثين موقفا ايجابيا نحو التعليم الإلكتروني مع تركيزهم على سلبياته ومعوقاته. _ ضعف استخدام الطلبة للمنصة بسبب المشكلات التي يطرحها استخدامها وحاجات المبحوثون: التي تمثلت في تحميل المحاضرات فقط، سيطرة القديم (الاعتماد على مصادر معلومات تقليدية: الأساتذة)، ومصادر أخرى بديلة ممثلة في صفحة القسم الرسمية. Abstract : Through this study, we seek to research students ' awareness of e-learning by focusing on their understanding of this topic and their actual response towards using one of its techniques, Moodle platform, was implemented. To achieve this, we conducted a field work using the free interview on an intentional sample of 22 students at the Department of Sociology, Faculty of Social Sciences, Tiaret University. We have reached the following main results: - The surveyed students have superficial knowledge with some distortions about elearning. - The surveyed students have a positive attitude towards e-learning with their focus on its disadvantages and obstacles. _ Poor use of the platform by students due to the problems posed by its use and the needs of researchers: which consisted in downloading lectures only, relying on traditional sources of information: professors, and other alternative sources represented on the official Department page.
دراسة ميدانية بقسم علم الاجتماع بجامعة تيارت
Keywords: التعليم الإلكتروني; منصة موودل; E -learning; Moodle platform; awareness; university studen